-4-7(5x-7)=49-39x

Simple and best practice solution for -4-7(5x-7)=49-39x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-7(5x-7)=49-39x equation:


Simplifying
-4 + -7(5x + -7) = 49 + -39x

Reorder the terms:
-4 + -7(-7 + 5x) = 49 + -39x
-4 + (-7 * -7 + 5x * -7) = 49 + -39x
-4 + (49 + -35x) = 49 + -39x

Combine like terms: -4 + 49 = 45
45 + -35x = 49 + -39x

Solving
45 + -35x = 49 + -39x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '39x' to each side of the equation.
45 + -35x + 39x = 49 + -39x + 39x

Combine like terms: -35x + 39x = 4x
45 + 4x = 49 + -39x + 39x

Combine like terms: -39x + 39x = 0
45 + 4x = 49 + 0
45 + 4x = 49

Add '-45' to each side of the equation.
45 + -45 + 4x = 49 + -45

Combine like terms: 45 + -45 = 0
0 + 4x = 49 + -45
4x = 49 + -45

Combine like terms: 49 + -45 = 4
4x = 4

Divide each side by '4'.
x = 1

Simplifying
x = 1

See similar equations:

| x-89=176 | | 2q-5=8q+1 | | X+52+90+90=360 | | x^2-X=43.32 | | 40=-5m-5 | | 64+x=146 | | X=25+24 | | 2m^(3)n^(6)/10m^(2)n^(3) | | -3x+51+15x=3 | | 14+r=26 | | X=17+4 | | x^2+10x+18=x | | 4(3n-1.2)-0.5=9.5+0.2 | | x+77=394 | | X=29-9 | | 25x-20=15x+15 | | 4d+13-6-13.20= | | 45=3s | | 2x+3y=1700 | | 25=17+m | | X=28+22 | | 3d+13-6-13.20=1.55 | | X=21+11 | | 3d+13-6-13.20=1.60 | | 128+x+40+82=360 | | x+5.25=7.55 | | X=19+11 | | 3d+13-6-13.20=2.07 | | X=28+14 | | 6=1.2 | | s-3.2=6 | | X=19+13 |

Equations solver categories